2021
DOI: 10.1108/lht-09-2020-0216
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective and prospective approaches of coronavirus publications in the last half-century: a Latent Dirichlet allocation analysis

Abstract: PurposeThe present article's primary purpose is the topic modeling of the global coronavirus publications in the last 50 years.Design/methodology/approachThe present study is applied research that has been conducted using text mining. The statistical population is the coronavirus publications that have been collected from the Web of Science Core Collection (1970–2020). The main keywords were extracted from the Medical Subject Heading browser to design the search strategy. Latent Dirichlet allocation and Python… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…ese topics were "structure and proteomics," "cell signaling and immune response," "clinical presentation and detection," "gene sequence and genomics," "diagnosis tests," "vaccine and immune response and outbreak," "epidemiology and transmission," and "gastrointestinal tissue" [62].…”
Section: Discussionmentioning
confidence: 99%
“…ese topics were "structure and proteomics," "cell signaling and immune response," "clinical presentation and detection," "gene sequence and genomics," "diagnosis tests," "vaccine and immune response and outbreak," "epidemiology and transmission," and "gastrointestinal tissue" [62].…”
Section: Discussionmentioning
confidence: 99%
“…Readers may also be interested in some related articles in Part I of our special issue. Danesh et al (2021) reported the topic modelling of the global coronavirus publications in the last 50 years with applied text mining and Latent Dirichlet allocation. Saab et al (2021) developed a deterministic model that quantifies previously adopted preventive measures driven by the reported number of deaths in Italy and India and used it to derive the optimal exiting policy using the inverse dynamics of the model.…”
Section: Research Funding and Bibliometric Researchmentioning
confidence: 99%
“…Therefore, the number of topics should be determined logically, with thematic expert advice, and according to the extent of the topic matter (32). The LDA algorithm also determines the optimal number of topics, the frequency distribution of documents in the selected topics, and the keywords list related to each topic; however, it cannot do automatic labeling, and hence, topic labels are defined and specified non-automatically (33). Therefore, the topics resulting from the LDA algorithm are labeled and interpreted using each topic's most important words and articles.…”
Section: Topic Modelingmentioning
confidence: 99%